2015
DOI: 10.1371/journal.pone.0130741
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Brachycephalic Obstructive Airway Syndrome in French Bulldogs Using Whole-Body Barometric Plethysmography

Abstract: Brachycephalic obstructive airway syndrome (BOAS) is an important health and welfare problem in several popular dog breeds. Whole-body barometric plethysmography (WBBP) is a non-invasive method that allows safe and repeated quantitative measurements of respiratory cycles on unsedated dogs. Here respiratory flow traces in French bulldogs from the pet population were characterised using WBBP, and a computational application was developed to recognise affected animals. Eighty-nine French bulldogs and twenty non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
180
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(191 citation statements)
references
References 27 publications
1
180
0
10
Order By: Relevance
“…Although multiple planned procedures have not been previously identified as a risk factor in brachycephalic dogs, prolonged anesthetic time, which is highly correlated with multiple procedures, has been identified as a risk factor for postanesthetic complications in brachycephalics . Obese dogs are reported to be 1.9‐fold more likely than dogs with normal body condition to show signs of BOAS, and severity of respiratory noise has been found to correlate with degree of airway function compromise …”
Section: Discussionmentioning
confidence: 99%
“…Although multiple planned procedures have not been previously identified as a risk factor in brachycephalic dogs, prolonged anesthetic time, which is highly correlated with multiple procedures, has been identified as a risk factor for postanesthetic complications in brachycephalics . Obese dogs are reported to be 1.9‐fold more likely than dogs with normal body condition to show signs of BOAS, and severity of respiratory noise has been found to correlate with degree of airway function compromise …”
Section: Discussionmentioning
confidence: 99%
“…Each dog was graded for functional severity of BOAS using a previously established 4‐point functional grading system (Table ) based on clinical evaluation before and after a 3‐minute exercise tolerance test (ETT) . BOAS functional Grade 0 dogs (asymptomatic, BOAS free) and Grade I dogs (mild BOAS, dog shows mild respiratory noise but exercise tolerance is unaffected) were considered clinically healthy for their breed.…”
Section: Methodsmentioning
confidence: 99%
“…Whole‐body barometric plethysmography (WBBP) is a non‐invasive technique of measuring respiratory function that has been validated and utilized in unrestrained unsedated experimental mice to characterize respiratory patterns during sleep and wakefulness . This technique has also been used in experimental and clinical studies using dogs and cats for pharmacological studies and respiratory disorders . Our previous study on French bulldogs showed that respiratory airflow characteristics obtained from WBBP are distinguishable between BOAS‐affected and clinically healthy French bulldogs .…”
mentioning
confidence: 99%
“…Although the large tongue of brachycephalic dogs is readily appreciable by oral examination, it has been noted uncommonly and inconsistently in the peer‐reviewed literature, and, when mentioned, it is typically unreferenced or cited as an earlier anecdotal observation . Possibly because of the lack of robust documentation, macroglossia is not listed as a feature of brachycephalism in many major veterinary texts, so awareness of it may be low in the veterinary profession .…”
Section: Introductionmentioning
confidence: 99%